A hybrid vapor chamber heat sink incorporating a vapor chamber and liquid cooling channel with outstanding thermal performance and hydraulic characteristics. (15th September 2021) - Wang, Huawei; Bai, Pengfei; Cai, Ruipeng; Luo, Yuhao; Chen, Xingliang; Li, Shixiao; Wu, Guodong; Tang, Yifan; Zhou, Guofu
Highlights: A hybrid vapor chamber heat sink with incorporating structure is proposed. The active cooling channel is embedded in the vapor region of a vapor chamber. The incorporating design weakens the temperature rise in the flow direction. The heat sink realizes a high coefficient of performance under high heat input. Abstract: Facing higher and higher heat load and more rigorous limitations on energy consumption, conventional heat sinks and vapor chambers are falling short of new requirements. In this paper, a hybrid vapor chamber heat sink (HVCHS) of liquid cooling is developed, wherein the active liquid cooling channel is embedded in the vapor region of the vapor chamber so that two modes of heat transfer, phase change and single-phase heat transfer, are incorporated in a single device. The thermal performance, hydraulic characteristics, and cooling coefficient of performance (COP) of the HVCHS are investigated. The hybrid design provides a high cooling capacity of 1200 W using a 9 cm 2 heater and maintains the maximum junction temperature of 95.25 °C simultaneously. The streamwise temperature rise is only 2.04 °C on the bottom surface under the maximum cooling capacity, which shows great temperature uniformity under high power. The minimum thermal resistance is as low as 0.04 °C/W and is compared with some previous studies. The minimum pressure drop is 4.83 kPa with the corresponding pump power of 80.5 mW. The cooling COP is above 12, 500 for heat inputs of more than 850 W. The HVCHS may have great potential for the energy-saving cooling management of high-performance electronics.